Peran Desainer Produk Interior dalam Meningkatkan Kesejahteraan Pengrajin Kerajinan dan Furnitur Pasca Pandemi - Grace Mulyono; Jochepine Cornelya Cristy (Society, 2023)
The creative industry is expected to drive economic growth in Indonesia after the COVID-19 pandemic. Abundant local materials and skilled human resources are two major strengths that need to be optimally managed to increase the selling value of design products. The pandemic has significantly impacted the welfare of furniture and handicraft artisans in Java. This paper aims to demonstrate the process and role of interior product designers (IPDs) in improving the socio-economic welfare of artisans after the pandemic. IPDs collaborated with Small and Medium Enterprises (SMEs), artisans, private entrepreneurs, governments, exporters, and associations to deal with vulnerabilities after the pandemic to achieve the development of policies and strategies toward sustainable community welfare. This IPDs role mainly focused on utilizing water hyacinth and rattan as the material for interior products to be accepted in local and global markets. The IPDs faced challenges in collaboration and unification of aspirations and interests between each party. The research used Kelley’s design thinking method, implementing the empathize, define, ideate, prototype, and test stages. The latest information on commodities produced by SME artisans, the existing advantages and disadvantages, and in-depth studies of developing market issues in Indonesia, Asia, and Europe were explored. The resulting design was then adjusted to the availability of raw materials, the production capabilities of the artisan, as well as the support of tools and technology used. The production process involved the government and industrial assistance in supporting the needs of machinery and production technology. Market tests at home country and abroad were conducted to determine the market response to the product. With a good market response, it is hoped that there will be policy development from the government and industry associations to support joint work to achieve a strategy for the socio-economic welfare of the community, especially groups of artisans.